Optimasi Kendali PID menggunakan Algoritma Genetika untuk Penerbangan Quadrotor - Khalaqas Hakiim; Andi Dharmawan; Faizah Faizah (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2017)
Quadrotor is square-form unmanned aerial vehicle (UAV) type with four motor in each arms. Quadrotor has ability to take-off and landing vertically. This research designs and creates a system that capable to stabilize the quadrotor flight also able to maintain roll, pitch and yaw angle using PID controller optimized by genetic algorithm, one of evolutionary algorithms.PID is a common applied controller including to control the quadrotor. Tunning or setting PID parameter process is needed to obtain fit PID parameters. Tunning is very important to reach quadrotor flight stability. This research applies Ziegler-Nichols tunning to obtain PID parameters. Then the PID parameters will be a reference for genetic algorithm optimization process to obtain the suitest PID parameter to control roll, pitch ,and yaw angle.Optimization process result show quadrotor controller capable to reach stability with steady state error for pitch angle in range 2,34 degree conterclockwise to 3,37 degree clockwise, for roll angle in range 2,99 degreee counterclockwise to 2,27 degree clockwise, and for yaw angle in range 8,39 degree counterclockwise to 3,89 degree clockwise.